Thyroid Cancer in Patients with Hyperthyroidism - Pazaitou-Panayiotou, K.; Michalakis, K.; Paschke, R. (Hormone and Metabolic Research, 2012)
Thyroid cancer can be associated with thyrotoxicosis caused by Graves’ disease, toxic multinodular goiter, or autonomously functioning thyroid adenoma. The objective of this study was to summarize current evidence regarding the association of thyroid cancer and hyperthyroidism, particularly with respect to the type of hyperthyroidism found in some patients, and whether this affects the outcome of the patient. A PubMed search was performed up to August 2011. Articles were identified using combinations of the following keywords/phrases: thyroid cancer, papillary thyroid cancer, follicular thyroid cancer, medullary thyroid cancer, anaplastic thyroid cancer, hyperthyroidism, Graves’ disease, autonomous adenoma, toxic thyroid nodule, and toxic multinodular goiter. Original research papers, case reports, and review articles were included. We concluded that the incidence, as well as the prognosis of thyroid cancer associated with hyperthyroidism is a matter of debate. It seems that Graves’ disease is associated with larger, multifocal, and potentially more aggressive thyroid cancer than single hot nodules or multinodular toxic goiter. Patients with Graves’ and thyroid nodules are at higher risk to develop thyroid cancer compared to patients with diffuse goiter. Every suspicious nodule associated with hyperthyroidism should be evaluated carefully.
Keywords: Graves’ disease; toxic multinodular goiter; hot nodules; hyperthyroidism; thyroid cancer